Bryophytes are not early diverging land plants. Issue 4 (10th March 2021) - McDaniel, Stuart F.
Summary: Phylogenetic trees have permeated biology. However, an understanding of how to interpret phylogenies has lagged behind, notably in publications outside of evolutionary biology. Here I argue that some language commonly used in plant systematics has contributed to the confusion by describing phylogenetic trees using intuitive but misleading terms reminiscent of Aristotle's Scala Naturae . These terms (perhaps inadvertently) misrepresent evolution, not as a process acting on all living species, but rather as a progression of successively diverging lineages leading to a group that represents a subjectively defined endpoint. My goal here is to show how thinking of the tree of life in terms of early‐diverging lineages and higher groups can distort evolutionary literacy, confound interdisciplinary communication, and potentially bias research agendas. I focus on the relationship between bryophytes and angiosperms as a case study, but the theme applies to all branches of the tree of life. Fortunately, evolutionary biologists have developed an easily understood alternative framework – tree thinking – which I highlight as a means to promote a clear understanding of phylogenies across sub‐disciplines of biology, and between practicing biologists and students, or members the public which funds much of our work.